2019
DOI: 10.3389/fnbeh.2019.00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Visuospatial Attention on the Sensorimotor Gating System

Abstract: The integration of multiple sensory modalities allows us to adapt to the environment of the outside world. It is widely known that visual stimuli interfere with the processing of auditory information, which is involved in the ability to pay attention. Additionally, visuospatial attention has the characteristic of laterality. It is unclear whether this laterality of visuospatial attention affects the processing of auditory stimuli. The sensorimotor gating system is a neurological process, which filters out unne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 22 publications
5
49
1
Order By: Relevance
“…In this pilot study, we investigated how repeated vmPFC-tDCS across 5 days affects the previously reported modulation of valence specificity [14,15,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this pilot study, we investigated how repeated vmPFC-tDCS across 5 days affects the previously reported modulation of valence specificity [14,15,27].…”
Section: Discussionmentioning
confidence: 99%
“…tDCS tDCS was applied by means of a DC Stimulator Plus (NeuroConn). The procedure was identical to previous studies [14,15,27]: in a two-electrode design with a 3 x 3 cm square electrode placed at 10-20 electrode position Fp and a 5 x 5 cm square electrode placed below the chin as extracephalic reference, a current strength of 1.5 mA was applied over 10 min. Both electrodes were covered in saline soaked sponges to enable sufficient conductibility.…”
Section: Participantmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The assimilation of pooled sensory modalities allows us to adapt to various environments. 37 PPI is the ability of a nonstartling pulse to inhibit responding to a subsequent startling "pulse" or stimulus. Deficits in sensorimotor gating, as measured by PPI, are well described in patients diagnosed with SCZ and other psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that CBD dose-dependently inhibits tau hyperphosphorylation in Aβ-simulated PC12 cells ( Esposito et al, 2006a ). Furthermore, CBD can increase cell survival, reduce Aβ-induced lipid peroxidation and reactive oxygen species production ( Iuvone et al, 2004 ), attenuate nitric oxide ( Esposito et al, 2006b ), and counteract the elevation of APP expression in transfected human neuroblastoma cells, thereby increasing cell survival ( Scuderi et al, 2014 ). In vivo , CBD has been found to attenuate Aβ-evoked neuroinflammation in a pharmacological mouse model of AD ( Esposito et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%